Inward Being and Outward Identity: The Orthodox Churches in the 21st Century - John A. Jillions (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The articles in this collection go well beyond introductions to look deeply at key dimensions of faith, theology, philosophy, liturgy, scripture, spiritual life and thinking on ecology and sexuality that together give a highly textured picture of the Orthodox Churches in the 21st century. The collapse of the Soviet Union has seen the Orthodox Church in Eastern Europe emerge from persecution to rebuild the infrastructure of churches, monasteries and social services and become a powerful cultural force. In contrast, Orthodox Christians in the Middle East and elsewhere are often caught in war, sectarian violence, duress and persecution. Meanwhile, in Western Europe, the Americas, Australia, parts of sub-Saharan Africa and other regions outside its traditional homelands Orthodox Christianity is taking hold as a distinct minority religion and attracting a steady stream of converts. But the faith is also struggling for its identity in cultural environments sometimes hostile to traditional Christianity. How are these churches engaged with secular society, other religions and other Christian churches? How well are Orthodox Churches listening and responding to the changing cultures they are living in? These are some of the fundamental questions being addressed here both theoretically and in case studies.